Ritual, remembrance and war: Social memory at Tyne Cot. (September 2015) - Winter, Caroline
Highlights: Evidence for the practices of remembrance involving linguistic ritual. Analysis of a large data set of the Tyne Cot Cemetery visitor book. Identification of one way in which tourists contribute to the process involved in social memory about the Great War. Development of the use of visitor books as data in identifying tourist experience. Linkage of theories of social memory with ritual and performance. Abstract: One of the social memories of the Great War of 1914–1918 focused on soldiers killed in battle, with military cemeteries forming important sites for remembrance. This paper reports the results of an analysis of the visitor books at Tyne Cot Cemetery in Belgium, that was built by the Commonwealth War Graves Commission to hold almost 12, 000 graves, most of which contain unidentified remains. Tourist's comments in the books evidenced a strong linguistic ritual, expressing sadness, gratitude, approval of the site and promises to remember and never forget the dead. Very little critique of war, or overt nationalistic sentiment was indicated. While some national preferences for ritualized phrases were shown, there was also an indication of a globally shared memory.